2016
DOI: 10.1089/lap.2015.0231
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Laparoscopy Could Be Better than Standard Laparoscopy in Right Colectomy for Cancer

Abstract: SIRC is feasible and sure for patients with colon cancer. As compared with SLRC, SIRC may offer some advantages, including lower operative morbidity, shorter hospital stay, and better cosmoses, without compromising the oncological quality of the resected specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Result showed that SIRC is feasible and sure for patients with colon cancer. As compared with SLRC, SIRC may offer some advantages, including lower operative morbidity, shorter hospital stay, and better cosmoses, without compromising the oncological quality of the resected specimen (35). A laparoscopic single-incision technique that is minimally invasive without requiring intracorporeal anastomosis was presented.…”
Section: Resultsmentioning
confidence: 99%
“…Result showed that SIRC is feasible and sure for patients with colon cancer. As compared with SLRC, SIRC may offer some advantages, including lower operative morbidity, shorter hospital stay, and better cosmoses, without compromising the oncological quality of the resected specimen (35). A laparoscopic single-incision technique that is minimally invasive without requiring intracorporeal anastomosis was presented.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported unexpected open conversion in SILS surgery, ranging from 1.4% to 9.5% 9,20,30,31 and insertion of an additional port ranging from 6.3% to 27.8% 18,32,33 . Conversion to open surgery is reported to increase postoperative complications, which results in longer hospital stays 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A single-entry point is placed, typically at the umbilicus, through which the laparoscope and all instruments are inserted [ 34 ]. Its efficacy and safety have been demonstrated across the spectrum of surgical disciplines [ 35 ].…”
Section: Discussionmentioning
confidence: 99%